A minimal sequence for left‐handed G‐quadruplex formation - Bakalar, Blaž (2020)
Recently, we observed the first example of a left‐handed G‐quadruplex structure formed by natural DNA, named Z‐G4 . We analysed the Z‐G4 structure and inspected its primary 28‐nt sequence in order to identify motifs that convey the unique left‐handed twist. Using circular dichroism spectroscopy, NMR spectroscopy, and X‐ray crystallography, we revealed a minimal sequence motif of 12 nt (GTGGTGGTGGTG) for formation of the left‐handed DNA G‐quadruplex, which is found to be highly abundant in the human genome. A systematic analysis of thymine loop mutations revealed a moderate sequence tolerance, which would further broaden the space of sequences prone to left‐handed G‐quadruplex formation.